People Development Dengan Metode Business Process Improvement (Studi Kasus: PT. XYZ) - Surbakti, Feliks Prasepta Sejahtera; Alfonso, Pedro (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
PT. XYZ intends to create a Human Resources Information System (HRIS), requiring HR master data. During the formation of HR master data, many errors were found in the business processes within it, necessitating corrections. The numerous errors in HR business processes have hindered the creation of the Human Resources Information System (HRIS) system. Business process improvements are carried out in the recruitment and people development modules. Improving business processes is the initial step in creating master data to be used in the Human Resources Information System (HRIS) system. Business process improvements begin with the identification of business processes, evaluation of business processes, and proposing business process improvements. The evaluation of business processes is done using the business process improvement method and the ESIA (Eliminate, Simplify, Integrate, Automate) technique. The proposed business processes for recruitment and people development show significant differences in the number of activities and the flow of processes performed